A miniaturization of microstrip antenna using negative permitivity metamaterial based on CSRR-loaded groundfor WLAN applications - Tung, Phan Duy; Lam, Phan Huu; Quynh Hoa, Nguyen Thi (Vietnam Journal of Science and Technology, 2016)
A microstrip antenna using negative index metamaterial based on complementary split ring resonator (CSRR)-loaded ground has been investigated in order to miniaturize the size and improve the antenna characteristics. The proposed antennas are designed on FR4 material and simulated results are provided by HFSS software. The metamaterial antenna was reduced 75 % the overall size compared to the normal microstrip antenna. Furthermore, compared with the normal microstrip antenna, the antenna characteristics of the metamaterial antenna were improved significantly. The proposed metamaterial antenna exhibited the antenna resonate at 2.45 GHz, the gain of higher than 6.5 dB and the bandwidth of 110 MHz through the whole WLAN band. The obtained results indicated that the proposed antenna is a good candidate for WLAN applications.